2012
DOI: 10.1186/1471-2334-12-326
|View full text |Cite
|
Sign up to set email alerts
|

The manual mycobacteria growth indicator tube and the nitrate reductase assay for the rapid detection of rifampicin resistance of M. Tuberculosisin low resource settings

Abstract: BackgroundTuberculosis (TB) is a disease of poverty that contributes significantly to ill-health in developing countries. Drug resistant TB is a major challenge to disease control. Early diagnosis and rapid determination of drug sensitivity is of paramount importance in eradication of TB. Although automated liquid culture based methods are available for rapid detection of drug resistance, the high cost of these tests prevent them from being used routinely in low resource settings. This study compares two pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The main objective of the article published by Adikaram et al [1] was to evaluate the suitability of the manual MGIT and the NRA for the rapid detection of rifampicin resistance in low-resource settings. Fourteen-day-old M. tuberculosis strains (n = 373) isolated onto solid media were used for DST by APM, NRA in liquid medium and the manual MGIT method.…”
Section: Summary Of Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main objective of the article published by Adikaram et al [1] was to evaluate the suitability of the manual MGIT and the NRA for the rapid detection of rifampicin resistance in low-resource settings. Fourteen-day-old M. tuberculosis strains (n = 373) isolated onto solid media were used for DST by APM, NRA in liquid medium and the manual MGIT method.…”
Section: Summary Of Methods and Resultsmentioning
confidence: 99%
“…To treat MDR-TB and XDR-TB patients, the classic 6-month treatment with first-line anti-TB drugs is not effective anymore, so they must be treated with less efficacious, more toxic and much more costly drugs [1]. The duration of treatment is up to 2 years.…”
Section: Key Paper Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The time to detection of a positive culture with MGIT was found to be shorter than with LJ or TLA, in accordance with the results of previous studies. [5][6][7][8][9][10][11][12][13][14] Furthermore, Balabanova et al reported that the concordance between drug susceptibility testing on LJ and MGIT was 96.8% for rifampicin and 95.6% for isoniazid. 28 There are new molecular techniques that perform well, allowing diagnosis on the same day, with the added advantage of providing information about resistance to isoniazid and/or rifampicin.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been shown to decrease the mean time to detection of growth to 11-15.1 days. 5,6,9,[11][12][13][14] The method of obtaining a respiratory sample is also critical. In prisons, it is important to employ alternative strategies to obtain a specimen when the patient cannot expectorate or has inadequate sputum (HIV patients or those with a dry cough), during follow-up to confirm that the patient is cured, or for people who are sputum smear-negative.…”
Section: Introductionmentioning
confidence: 99%